Lenvatinib and tislelizumab versus atezolizumab and bevacizumab in combination with TAE-HAIC for unresectable hepatocellular carcinoma with high tumor burden: a multicenter retrospective cohort study - Hongjie Cai; Song Chen; Shuangyan Tang; Yi Xiao; Feng Shi; Zhiqiang Wu; Ping Ma; Huanwei Chen; Wenquan Zhuang; Wenbo Guo (Cancer Immunology, Immunotherapy)
Abstract Background Systemic and locoregional combination therapy has demonstrated promising outcomes for unresectable hepatocellular carcinoma (HCC); However, the best combination option remains unknown. This study compared the efficacy and safety of lenvatinib and tislelizumab versus atezolizumab and bevacizumab in combination with transarterial embolization (TAE) plus hepatic artery infusion chemotherapy (HAIC) for unresectable HCC with high tumor burden. Methods This multicenter retrospective cohort study enrolled treatment-naive patients with unresectable HCC treated with TAE-HAIC plus lenvatinib and tislelizumab (THLP group) or TAE-HAIC plus atezolizumab and bevacizumab (THTA group). The primary endpoint was overall survival (OS). Secondary endpoints included progression-free survival (PFS), tumor response, and adverse events (AEs). Propensity score matching (PSM) was performed to reduce bias. Results Of the 240 patients enrolled, 153 and 51 patients were assigned to the THLP and THTA groups, respectively after PSM (3:1). The THLP group showed a longer median OS (22 months vs. 18.2 months; P = 0.412), whereas the median PFS was longer in the THTA group (8.1 months vs. 7 months; P = 0.723), with statistically insignificant intergroup differences. No statistical differences were observed in objective response rate (RECIST 1.1: 33.9 vs. 31.4%; mRECIST: 77.1% vs. 74.5%; P = 0.635), disease control rate (RECIST 1.1: 88.9% vs. 92.2; mRECIST: 92.2% vs. 94.1%; P = 0.716), and in grade 3/4 AEs. Gastrointestinal hemorrhage rate was significantly higher in the THTA group (9.1% vs. 1.6%; P = 0.007). All AEs were controllable and no treatment-related grade 5 AEs occurred. Conclusions TAE-HAIC plus lenvatinib and tislelizumab or TAE-HAIC plus atezolizumab and bevacizumab showed similar outcomes for unresectable HCC with high tumor burden, and manageable safety. The results need further validation.